Nupcialidad, compadrazgo y endogamia en las Yungas de Jujuy (Noroeste de Argentina) durante la primera mitad del siglo XIX - Juan Pablo Ferreiro; Federico Fernández (Caravelle)
This paper explores and analyzes the particular relationship that occurred historically among the main recruitment devices parental-real and symbolic, bridal and godfatherood habitus in a marginal and relatively isolated area characterized by strong inbreeding, in the region of Valle Grande (Jujuy Province, Argentina) during the first half of the nineteenth century. So, we implemented a strategy based on the so-called structural analysis that allows us to rebuild the interaction between individuals and discrete sets versus absence of statistics, or local memories and stories from the certifying of marriage and baptism records.